Price relationships and market integration: a Northeast of Brazil case study - Mayorga Mera, Ruben Dario (1989)
This dissertation explores price interdependence among the wholesale tomato markets in Northeast Brazil. The markets for tomatoes have recently increased in importance both for producers in the Serra da Ibiapaba and for consumers in the capital cities of Fortaleza, Teresina, and São Luis. The markets in these cities include a range of entrepreneurs from small and poorlycapitalized middlemen to large truck owners and integrated urban wholesalers with various categories between these extremes. The inherent risk involved in vegetable markets due to price variations, perishable commodities and insufficient local infrastructure determine the behavioral strategies of farmers and intermediaries. To determine whether prices in a specific market behave interdependently with prices in other markets, the Granger causality method was applied using weekly price data for wholesale markets in Fortaleza, Teresina and São Luis. The results of this dissertation support, in general terms, the conclusion that prices in the wholesale markets of Fortaleza, Teresina and São Luis function as integrated (markets, implying a competitive nature of the Northeast tomato market. Statistical evidence suggests that Fortaleza operates as a central market "driving" the prices of Teresina and São Luis. The lack of directly contemporaneous causality between Fortaleza. and São Luis indicated the presence of imperfections in these markets. This results were expected due to the strategies of intermediaries who increase prices as a means to cover possible payment default in Sao Luis, and the lack of bargaining power of intermediaries in Fortaleza. Also, the longer distance that separates these markets may cause price adjustment in time periods different than contemporaneous. Other studies suggest that governments have a role in promoting competition among markets and monitoring and implementing plans created to improve the marketing system. Market imperfections in the system can be reduced by adequate market information to diminish the risk associated with intermarket trade. In the tomato markets of Northeast Brazil policies promoting increased supply during the winter season and enforcing payment of the commodities commercialized in the CEASAs are needed simultaneously with technical measures to provide high quality seeds and facilitate storage.